Sex role stereotyping and education - the Jamaican perspective - Leo-Rhynie, Elsa (1979)
This paper examines whether the Jamaican woman is still a symbol of "conspicuous consumption," restrained by Westernized sex-role stereotyping, which limits her to child-rearing and certain lower-order vocations. It questions whether she is assured of such things as adequate educational opportunities, accessibility to rewards for efforts, and an environment that provides incentives to even greater efforts
doi: 10.1007/BF01191439
Keywords: Women's status